Broadband Pattern Diversity Patch Antenna With Switchable Feeding Network - Xujun Yang; Huawei Lin; Hui Gu; Lei Ge; Xierong Zeng (IEEE Access, 2018)
A single-feed wideband pattern diversity antenna is presented in this paper. the pattern reconfigurability is realized by a p-i-n-diodes-intergrated switchable feeding network with the ability of providing 0° in-phase or 180° out-of-phase antenna excitation. the radiating patch is excited by the feeding network through a pair of symmetric stepped probes. when the two stepped probes are with in-phase excitation, a conical mode can be generated on the patch. on the other hand, the antenna can operate at a broadside mode if the excitation is out-of-phase. a meticulous prototype is developed, manufactured, and measured. the measured impedance bandwidths of the 10-db return loss are 60.7% from 1.95 to 3.65 ghz for the broadside mode and 72.7% from 1.65 to 3.65 ghz for the conical mode. meanwhile, measured peak gains of up to 10.2 and 7.7 dbi and measured radiation efficiencies of higher than 80% and 76% are obtained for the broadside mode and conical mode, respectively.